Muzykowanie z fińskim akcentem. Edukacja muzyczna w nauczaniu początkowym w Finlandii - Adamczewski, Jakub (Studia Edukacyjne, 2019)
The article highlights the meaning of music activities in early childhood education. All the personal thoughts and information are mostly based on the Finnish educational system and the examples coming from my teaching practice at Vasa Övningsskola. Music education has an enormous impact on the child’s development at early school age. The way we teach and the teacher’s personality play a key role in the process of self-learning. This article contains both theoretical and practical aspects of music education in Finnish primary schools. The conclusion is supported by personal experience and observations from a Finnish primary school, which help to precisely describe music education in this particular system. The speaker will present activities and ideas used in the music education in early school age based on the national curriculum from 2016.